Photoactive film by covalent immobilization of a bacterial photosynthetic protein on reduced graphene oxide surface. Issue 1717 (5th February 2015) - Tangorra, Rocco Roberto; Antonucci, Alessandra; Milano, Francesco; Operamolla, Alessandra; Italiano, Francesca; Ragni, Roberta; Omar, Omar Hassan; Salice, Patrizio; Silvestrini, Simone; Menna, Enzo; Maggini, Michele; Agostiano, Angela; et al.
ABSTRACT: Covalent functionalization of reduced graphene oxide (rGO) with the photosynthetic reaction center (RC) from Rhodobacter sphaeroides R26 via click chemistry reaction has been performed. The hybrid system was characterized by flash photolysis and infrared spectroscopy and the RC was found to retain its photoactivity and structural integrity. The strategy is applicable for the fabrication of hybrid bio-electronic devices capable of absorbing and converting solar energy.